Assessing the Social Impact of Immigration in Europe Renegotiating Remoteness - Laine, Jussi P.; Rauhut, Daniel; Gruber, Marika (Edward Elgar Publishing, 2023)
Focusing on the social impact of migration, this book explores migration as an inevitable part of rural development and transition in light of the sharp political divides in European and national political arenas on the topic. It provides an innovative immigration impact assessment based on recently conducted empirical work to enhance local development in European rural and remote regions, looking to promote change in the perception of migration and related policies and practices.